The Wages of Fear: Risk, Safety and Undocumented Work - Jon Burnett (Positive Action for Refugees and Asylum Seekers (PAFRAS) and the University of Liverpool, 2010)
This report presents a study of precarious working conditions experienced by undocumented workers in the north of England. It begins by exploring the importance of notions of labour market flexibility and flexicurity in government and trans-national government policy making. It argues that the exploitation of migrant workers and undocumented workers is structured by these labour market conditions. Second, it utilises interview data to consider in detail this structural subordination, arguing that, combined with the at times contradictory imperatives of immigration policy, the precariousness of undocumented workers acts as a disciplinary tool. Finally, it indicates that, in this context, the occupational risks to which undocumented workers are exposed need to be understood in terms of the highly dangerous and violent consequences experienced by those workers.